7 Sex differences in late chemotherapy-induced cardiomyopathy in adult cancer survivors: a cardiovascular magnetic resonance study. (18th May 2017) - Harries, Iwan; Biglino, Giovanni; Dastidar, Amardeep Ghosh; Baritussio, Anna; DeGarate, Estefania; Kestenbaum, Samantha; Williams, Matthew; Seyani, Chitsa; Brady, Paul; Chai, Jason; Richards, Gavin; Bracken, Jennifer; et al.
Abstract : Introduction: Chemotherapy induced cardiomyopathy (CIC) carries significant morbidity and mortality in cancer survivors. Female sex is a recognised risk factor for CIC in paediatric populations but the effect of sex in adult patients has not been established. We investigated sex differences in CIC using cardiovascular magnetic resonance (CMR). Method: 76 patients without abnormal left ventricular function prior to chemotherapy (30 male [59±15 years], and 46 female [58±13 years, p=0.86]) were included. Cumulative anthracycline dose (193±165 vs. 189±119 mg/m 2, p=0.91) and follow-up interval (8.75±8.75 years vs. 8.75±9 years, p=0.99) were similar. All patients underwent contrast-enhanced CMR at 1.5T, including long and short axis cine imaging, mitral and tricuspid annular peak systolic excursion (MAPSE and TAPSE, respectively), and late gadolinium enhancement (LGE). Multivariate regression analysis was undertaken. Results: Left (39±13 vs 46±10%; p=0.027) and right ventricular ejection fraction (50±10 vs. 55±8%; p=0.042) were significantly lower in males, largely driven by differences in LV (208±83 vs. 167±42, p=0.02) and RV end diastolic volume (150±44 vs. 120±31, p=0.002). MAPSE and LAVi correlated significantly with LVEF (p<0.001 in both cases), as did TAPSE with RVEF (p=0.02). LGE prevalence did not differ between males and females (37% vs. 20%, respectively, p=0.10). Conclusions: Adult male cancer survivors developed comparably worse late biventricular CIC than their female counterparts despite receiving similar doses of cancer treatment. These findings need confirmation in larger cohort studies, and if confirmed, could inform bespoke monitoring strategies taking sex differences into account.